ZPA Regulatory Sequence Variants in Chinese Patients With Preaxial Polydactyly: Genetic and Clinical Characteristics - Zeng, Lei; Jin, Jie-Yuan; Luo, Fang-Mei; Sheng, Yue; Wu, Pan-Feng; Xiang, Rong (Frontiers in Pediatrics, 2022)
Preaxial polydactyly (PPD) is a common congenital abnormality with an incidence of 0.8–1.4‰ in Asians, characterized by the presence of extra digit(s) on the preaxial side of the hand or foot. PPD is genetically classified into four subtypes, PPD type I–IV. Variants in six genes/loci (including GLI3, ZRS, and pre-ZRS region) have been identified in PPD cases. Among these loci, ZRS is perhaps the most special and well-known, but most papers only reported one or a few cases. There is a lack of reports on the ZRS-variant frequency in PPD patients. In this study, we recruited 167 sporadic or familial cases (including 154 sporadic patients and 13 families) with PPD from Central-South China, and identified four ZRS variants in four patients (2.40%, 4/167), including two novel variants (ZRS131A>T/chr7:g.156584439A>T and ZRS474C>G/chr7:g.156584096C>G) and two known variants (ZRS428T>A/chr7:g.156584142T>A and ZRS619C>T/chr7:g.156583951C>T). ZRS131A>T and ZRS428T>A were detected in PPD I cases, and ZRS474C>G and ZRS619C>T combinedly acted to cause PPD II. The detectable rate of ZRS variants in PPD I was 1.60% (2/125), while PPD II was significantly higher (9.52%, 2/21). Three bilateral PPD cases harbored ZRS variants (13.64%, 3/22), suggesting that bilateral PPD was more possibly caused by genetic etiologies. Our study identified two novel ZRS variants, further confirmed the association between ZRS and PPD I, and reported a rare PPD II case resulted from the compound heterozygote of ZRS. Our investigation preliminarily evaluated a ZRS variants rate in PPD patients and described the general picture of PPD in Central-South China.